(624) Directory of Periodicals at the INP Documentation Center - محمد عويضة (معهد التخطيط القومى, 2026)
هذا الملف هو عبارة عن دليل للمجلات والدوريات العلمية المتوفرة في مركز التوثيق التابع لمعهد التخطيط القومي بالقاهرة، والذي صدر في عهد "الجمهورية العربية المتحدة". يتضمن الدليل قائمة منظمة لمجموعة واسعة من المطبوعات الدورية في تخصصات متنوعة تشمل الاقتصاد، والزراعة، والمحاسبة، وعلوم الحاسب، والإحصاء، والعلوم السياسية، وغيرها من المجالات التنموية والاجتماعية التي تخدم أغراض البحث العلمي والتخطيط. يوفر الدليل بيانات تفصيلية لكل دورية، مثل جهة الإصدار، وبلد المنشأ، وتاريخ المجلدات أو الأعداد المتاحة، بالإضافة إلى وتيرة صدورها (شهرية، ربع سنوية، أو سنوية). ويظهر من خلال محتوياته اعتماد المركز على مصادر دولية ومحلية متنوعة، حيث يشمل مجلات من منظمات عالمية مثل منظمة الفاو والبنك الدولي، إلى جانب إصدارات بنوك ووزارات مصرية وعربية، مما يجعله مرجعاً توثيقياً شاملاً للباحثين في تلك الحقبة الزمنية. This document is a Directory to Periodicals available at the I.N.P. Documentation Center in Cairo, prepared by Mohammed Ewieda and supervised by Mahmoud Eid. It serves as a comprehensive guide for researchers, categorizing a vast collection of academic and professional journals under various subjects such as Accounting, Economics, Statistics, and International Trade. The directory provides essential bibliographic details for each entry, including the publisher's name, location, frequency of publication, and the specific years available in the center's collection, ranging mostly throughout the late 1950s and early 1960s. By indexing both local and international sources—from the Central Bank of Egypt to the United Nations—this directory highlights the center's role as a vital hub for information and research during that period.